Selective and caspase-independent cytotoxicity of bioactive glasses towards giant cell tumor of bone derived neoplastic stromal cells but not to bone marrow derived stromal cells - Westhauser, Fabian; Arango-Ospina, Marcela; Losch, Sarina; Wilkesmann, Sebastian; Lehner, Burkhard; Ali, Muhammad S.; Peukert, Wolfgang; Boccaccini, Aldo R.; Fellenberg, Jörg (Biomaterials, 2021)
Semi-malignant giant cell tumors of bone (GCTB) are associated with large osteolytic defects and significant bone destructions. Surgical resection remains the standard therapy that is, however, associated with very high recurrence rates. Bioactive glasses (BGs) that are osteogenic but under certain conditions also cytotoxic might be suitable to achieve biological reconstruction with simultaneous reduction of tumor recurrence in GCTB. In this study, a concentration and time dependent cytotoxic effect of five different BG compositions towards neoplastic GCTB cells was identified while bone marrow derived mesenchymal stromal cells were mostly unaffected. Time course and extent of the cytotoxic effect were dependent on the BG composition and were not associated with caspases activation, indicating that apoptotic mechanisms are not involved. Rather, detection of BG-induced disruption of the cell membranes and a rapid drop of intracellular HMG1 (High Mobility Group Box 1 protein) levels suggest a necrotic cell death. Notably, the cytotoxic effects were dependent on a direct contact of cells and BGs and could not be observed using indirect cultivation settings. Our data suggest that BGs might represent promising materials for the treatment of GCTB in order to reduce tumor recurrence with simultaneous enhancement of bone regeneration.
Gesehen am 04.09.2021